Effect of Drying Temperature and Slice Thickness on Drying Kinetics, Moisture Diffusivity, Energy Use, and Color Change in Convectively Dried Chayote Squash Slices - Nurkhoeriyati, Tina; Rustandi, Ignatius Arya Krishna; Mwape, Mwewa Chikonkolo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Insufficient fiber intake is strongly associated with chronic diseases. Chayote squash (Sechium edule), widely available in Indonesia, has potential as a fiber source, and drying provides a practical method for its use in food products. This study evaluated the drying kinetics, specific energy consumption (SEC), total color change (ΔE*ab), and effective moisture diffusivity (Deff) of chayote slices under different temperatures (50, 60, and 70 °C) and thicknesses (3 and 6 mm) to determine the optimum drying conditions. Drying time (DT) ranged from 150 min (70 °C, 3 mm) to 350 min (50 °C, 6 mm). The approximation of diffusion and the Midilli and others models best represented the drying kinetics. The highest SEC was 3.40×10⁶ kJ·kg⁻¹ (60 °C, 3 mm), while other treatments showed no significant differences. Deff increased with temperature and thickness (3.38×10⁻¹⁰ to 1.28×10⁻⁹ m²·s⁻¹). Food color, an important factor influencing consumer acceptance, showed no significant ΔE*ab differences across treatments. The optimum drying condition determined was 70 °C with 3 mm slices (DT of 149 min, ΔE*ab of 16.62, SEC of 3.02×10⁶ kJ·kg⁻¹). These findings provide insights into designing chayote drying processes that achieve desirable quality while minimizing energy consumption.